Canadian banks' responses to COVID-19: a strategic positioning analysis. (3rd April 2022) - Talbot, David; Ordonez-Ponce, Eduardo
ABSTRACT: The Canadian banking system is among the best in the world. Amid the COVID-19 pandemic, the world is challenged and banks are expected to rescue society. Businesses are revising, repurposing, and reinventing their products and services to address people's needs. In this context, this article seeks to understand how Canada's banks are supporting their clients and communities, during the current health crisis. Content analysis was conducted to analyse Canada's ten largest banks' supporting actions towards the pandemic, leading to 125 documents and 19 different actions consulted. Based on the data, a combination of hierarchical clustering and multidimensional scaling was conducted. Following a CSR approach, three clusters of banks are identified: sweeping actions, cautious actions, and wait & see, highlighting that while most banks are doing little to help their stakeholders, three of them have a proactive and strong commitment to their clients and communities in these times of need.